ANALYTICAL STUDY OF THE IMPLEMENTATION AND EFFECTIVENESS OF THE SWAMI VIVEKANAND GOVT. MODEL SCHOOLS ESTABLISHED IN THE EBBS OF RAJASTHAN STATE - Yadav, Suresh Kumar; Nagar, Dr. Alpa (International Journal of Research -GRANTHAALAYAH, 2025)
The main purpose of the study was to study the Various Aspects of Swami Vivekanand Govt. Model Schools Established in EBBs of Rajasthan. For this a total of 20 schools from 12 districts (Pali, Jodhpur, Jaisalmer, Dungarpur, Udaipur, Rajsamand, Bhilwara, Dausa, Tonk, Sawai Madhopur, Jaipur, Ajmer) of Rajasthan were selected by random method. After analysed the data the researcher observed both positive and negative conditions in Swami Vivekananda Model Government Schools. Some schools faced issues like teacher shortages, insufficient budgets, lack of facilities, and excessive workload. Others showcased excellence with strong community support, ATL labs, smart classrooms, regular surveys and meetings, and student achievements at the national level. Despite lacking government internet support, some headmasters arranged it independently. Overall, school conditions varied significantly.